Left ventricular size as a predictor of outcome in patients of non-ischemic dilated cardiomyopathy with severe left ventricular systolic dysfunction. (15th October 2016) - Gupta, Ankur; Sharma, Prafull; Bahl, Ajay
Abstract: Background: Limited data is available regarding prognosis of patients with severe left ventricular (LV) systolic dysfunction and varying LV dimensions. Purpose of this study was to compare outcomes of patients with non-ischemic dilated cardiomyopathy (DCM) with respect to LV size. Methods: 145 patients of DCM cohort with LV ejection fraction < 35% were divided into 3 groups. Group 1 with normal LV dimensions, group 2 with mild-moderately enlarged left ventricle and group 3 with severely dilated left ventricle. Primary endpoint was composite of all cause mortality and heart failure hospitalizations at end of follow-up. Results: Forty-four patients (30.3%) with normal LV diastolic diameter (51.9 ± 5.3 mm) were included in group 1, 57(39.3%) with mild-moderately enlarged LV (61.4 ± 3.7 mm) in group 2 and 44(30.3%) with severely enlarged LV (71.3 ± 7.4 mm) in group 3. Mean follow-up was 42.2 ± 31.6 months. Primary end point occurred in 4 patients (9.1%) in group 1, 8 patients (14%) in group 2 and 9 patients (20.5%) in group 3, p = 0.23 by log-rank test. Hazard ratio for primary endpoint in group 2 as compared to group 1 was 1.71(95% CI, 0.51 to 5.67; p = 0.39) and in group 3 as compared to group 1 was 1.61(95% CI, 0.89 to 2.91; p = 0.11). Of patients with more than two years of follow-up, 2 of 29 patients(6.9%) died in group 1, 3 of 35 patients(8.6%) in group 2 and 3 of 34 patients(8.8%) died in group 3, p = 0.95. Conclusions: Intermediate term prognosis of patients with severe LVSD and severely dilated left ventricle is good, with outcomes similar to patients with normal or mild-moderately dilated left ventricle.